Penerapan Komunikasi Vertikal Antara Pimpinan Dan Karyawan Dalam Membangun Kepuasan Kerja Di Divisi Spare Part Astra Motor Main Dealer Kota Bengkulu - Kurniati, Dian; Adhrianti, Lisa; Firmansyah, Mas Agus (STAI Bumi Silampari, 2025)
This study aims to determine the application of vertical organizational communication between leaders and employees in building job satisfaction in the Spare Parts Division of PT Astra Motor Main Dealer, Bengkulu City. Using a qualitative approach with a case study method and purposive sampling technique, data were collected through interviews, observations, and documentation. The results of the study indicate that the application of vertical communication between leaders and employees in the Spare Parts Division of PT Astra Motor Main Dealer, Bengkulu City has been running quite well but still faces several obstacles. Vertical communication is carried out in two directions, namely communication from leaders to subordinates (downward communication) and from subordinates to leaders (upward communication). When communication is carried out openly, clearly, and two-way, employees feel more appreciated, better understand the tasks assigned, and are more motivated to contribute to achieving company goals. However, there are still obstacles that hinder the effectiveness of communication, such as delays in information, lack of feedback from superiors, and miscommunication that arises due to differences in perception between leaders and subordinates. Therefore, efforts are needed to improve the quality of communication through openness, timely delivery of messages, and strengthening two-way communication channels so that vertical communication can function optimally in building employee job satisfaction.